Sources and pathways of spread of vancomycin-resistant enterococci in hemato-oncological patients - Vagnerova, Iva; Sauer, Pavel; Kolar, Milan; Slepickova, Sabina; Hubacek, Jaromir; Faber, Edgar; Raida, Ludek; Papajik, Tomas (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2006)
The presented study aims at analyzing an increasing prevalence of vancomycin-resistant enterococci (VRE) isolated from various kinds of clinical material obtained from patients in the Department of Hemato-oncology (DHO), University Hospital in Olomouc, Czech Republic. Between January 1 and March 31, 2005, enterococci were isolated by standard microbiological procedures using both clinical material obtained from hospitalized patients and samples from the department environment. Resistance to vancomycin and teicoplanin was determined by a standardized microdilution method. Phenotype determination of resistance to vancomycin was verified by PCR detection of vanA and vanB genes. In VanA Enterococcus faecium, macrorestriction analysis was performed by pulsed-field gel electrophoresis. During the monitored period, a total of 128 Enterococcus sp. strains were isolated, of which 38 (30 %) isolates from 22 different patients were determined as VRE. Dominating were Enterococcus faecium VanA (63 %) and Enterococcus casseliflavus VanC (16 %) strains. At the same time, one Enterococcus faecium VanA strain was acquired from a bed-side table used by a patient in whom a similar strain had been isolated repeatedly from various clinical materials including a rectal swab taken in 2004. Based on the macrorestriction analysis of genome DNA in 24 vancomycin-resistant Enterococcus faecium VanA strains isolated from the patients' clinical material, one strain from the bed-side table surface and one strain isolated from stools in 2004, 8 unique restriction profiles with similarity ranging from 90 % to 100 % were identified, which could be classified into 3 clonal types. Thus, we can assume not only the endogenous origin of the VRE in hemato-oncological patients and their potential selection caused by therapy with broad-spectrum antibiotics but also the ability of the strains to survive in a hospital setting and, subsequently, to be spread clonally by various vectors.
Keywords: infekce spojené se zdravotní péčí; Teicoplanin; grampozitivní bakteriální infekce; Cross Infection; Enterococcus; lidé; Vancomycin Resistance; Gram-Positive Bacterial Infections; Drug Resistance, Bacterial; hematologické nádory; Hematologic Neoplasms; teikoplanin; rezistence na vankomycin; bakteriální léková rezistence; Humans